1999
DOI: 10.1046/j.1365-3016.1999.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in birthweight for gestational age and infant mortality in extremely‐low‐risk US populations

Abstract: Using national data, we develop and contrast the birth-weight percentiles for gestational age by infants of extremely-low-risk (ELR) White and African-American women and examine racial differences in the proportion of small-for-gestational-age (SGA) births. We then scrutinise racial variations in infant mortality rates of the infants of ELR women. We further compare the infant mortality rates of infants at or below the 10th percentile of birthweight for gestational age of each race group to determine whether i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(76 citation statements)
references
References 58 publications
2
73
1
Order By: Relevance
“…26 The studies showed that, despite their higher rates of small-for-gestational-age infants based on a single standard, these infants did not have a higher risk of adverse outcomes. Whereas previous studies assessed the impact of maternal birthplace or ethnicity on small for gestational age, [24][25][26] we simultaneously evaluated the impact of maternal origin on large for gestational age and on a wide array of outcomes including neonatal death, thus generating a more complete picture.…”
Section: Discussionmentioning
confidence: 99%
“…26 The studies showed that, despite their higher rates of small-for-gestational-age infants based on a single standard, these infants did not have a higher risk of adverse outcomes. Whereas previous studies assessed the impact of maternal birthplace or ethnicity on small for gestational age, [24][25][26] we simultaneously evaluated the impact of maternal origin on large for gestational age and on a wide array of outcomes including neonatal death, thus generating a more complete picture.…”
Section: Discussionmentioning
confidence: 99%
“…36 When compared with earlier reports, these data suggest that substantial improvements in neonatal mortality have occurred, particularly among LBW and preterm infants. 4,34,35,37 Notwithstanding, additional research is needed to determine how these improvements have affected the disparities in newborn survival between ethnic/racial groups and to identify where there has been a lack of progress. This study provides a foundation with which to examine these issues while providing reference data to assist physicians who work with newborns at the extreme limits of viability.…”
Section: Discussionmentioning
confidence: 99%
“…"Small for gestational age" or "intrauterine growth retardation" can result in reduced birth weight for any given gestational age and may Figure 2 Cumulative percent of the racial disparity in neonatal mortality by birth weight category: United States, 1999. Source: (29) have different implications for subsequent morbidity and mortality (1). Although worthy of some analytic caution, birth weight continues to be used constructively as a general proxy for gestational age, particularly for birth weight categories contributing most heavily to disparate infant outcomes.…”
Section: The Impact Of Technical Interventionsmentioning
confidence: 99%